2018
DOI: 10.1515/ijamh-2018-0133
|View full text |Cite
|
Sign up to set email alerts
|

Level, motivation and barriers to participate in physical activity among late adolescents in Puducherry

Abstract: Background One in every ten deaths globally is accounted for by physical inactivity-related risks. Adolescents constitute 18% of the world’s total population and are at risk of becoming physically inactive in the future. Thus, this study aims to find the level of physical activity (PA) among late adolescents and factors that motivate and prevent them from being active. Methodology Four hundred and fifty adolescents in the age group of 18–19 years were included in the study. Standardized self-administered que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Divyasree et al 17 conducted a study among adolescents in Puducherry revealed that one-third of late adolescents are insufficiently physically active in the adolescents was 31% respectively. Studies done by Kumar et al 18 revealed that 64% of the adolescents had an insufficient PA level, but our study supports the fact that late adolescents are doing sufficient physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Divyasree et al 17 conducted a study among adolescents in Puducherry revealed that one-third of late adolescents are insufficiently physically active in the adolescents was 31% respectively. Studies done by Kumar et al 18 revealed that 64% of the adolescents had an insufficient PA level, but our study supports the fact that late adolescents are doing sufficient physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…8 The sample size was estimated as 450 based on the prevalence of low physical activity to be 31% from literature. 9 The sample size was calculated to be 836 with 95% confidence and 5% absolute precision, design effect as 2.5 using OpenEpi software. Assuming 10% non-response or incomplete questionnaires, the final 920 sample size was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…These findings were in accordance with studies conducted by Kundapur et al in Mangaluru, Guthold et al, Divyasree et al in Puducherry and Esht et al in Punjab. [11][12][13][14] The gender difference may be because parents or family members of a female adolescent discourage them to play outside with fear of harm, bullying or teasing etc. Also, female adolescents may find it difficult to get involved in moderate to vigorous physical activity being in the first…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire consisting of 36 items was prepared by the researcher based on review of literature. [5][6][7][8] It was face validated by subject expert faculty members and had good internal consistency (Cronbach's alpha=0.886). The 36 items were grouped into 6 main categories-Physical, mental, college/ work related, environmental, social and others.…”
Section: Instrumentmentioning
confidence: 99%